Assessment of possibilities of ceramic biomaterial fracture surface reconstruction using laser confocal microscopy and long working distance objective lenses. Issue 5 (26th February 2016) - Stach, Sebastian; Sapota, Wiktoria; Wróbel, Zygmunt; Ţălu, Ştefan
ABSTRACT: A numerical description of fracture is an important step in the search of the correlation between specific micromechanisms of decohesion and material characteristics designated with the use of fracture mechanics methods. This issue is essential for the proper orientation of the search for basic relationships between chemical composition, technology, structure, and properties of materials. It often happens that fracture surfaces are well developed, which can significantly hinder or even prevent the measurement and reconstruction of the tested material surface geometry. In this article, comparative measurements of a biomaterial surface were performed using laser confocal microscopy. To this end, short working distance lenses dedicated to a focused UV laser beam and long working distance objective lenses were used. The article includes a quantitative comparative analysis and interpretation of the obtained results. Microsc. Res. Tech. 79:385–392, 2016 . © 2016 Wiley Periodicals, Inc.